Preparation and Evaluation of Self-micro Emulsifying Drug Delivery Systems of Lercanidipine HCl using Medium and Short Chain Glycerides: A Comparative Study - Butani, Dr. Shital B. (Asian Journal of Pharmaceutics (AJP), 2016)
Aims: The aim of this study was to formulate a self-microemulsifying drug delivery system (SMEDDS) of Lercanidipine HCl (LCH) using medium chain (MC) and short chain (SC) glycerides as oil phase and to compare the dissolution efficiency of both formulations. Materials and Methods: Different oils and surfactants containing MC and SC fatty acid as basic molecule were screened using quantitative solubility study and constructing pseudoternary phase diagrams. Cosolvents were used as cosurfactants. The preconcentrates were tested for a self-microemulsifying time, % transmittance, cloud point, globule size, zeta potential, and in-vitro drug release. Selected formulations were compared by calculating dissolution efficiencies in different pH media. Results: Capmul MCM, CremophorÂ® RH 40, and polyethylene glycol 400 were chosen as oil, surfactant, and cosurfactant, respectively, for MC glyceride and triacetin and Tween 80 were selected as oil and surfactant for SC triglyceride category, respectively. All the formulations spontaneously resulted into transparent microemulsion with globule sizes range from 50 to 90 nm for MC-SMEDDS and 200-317 nm for SC-SMEDDS. The formed microemulsions were stable as shown by zeta potential and cloud point determination. However, in-vitro drug release in 0.1 N HCl showed quite a similar dissolution of all the formulation batches, a study in the different pH media showed that LCH being weak base, possess pH dependent solubility. Conclusions: The MC-SMEDDS were able to resist the effect of pH on dissolution to some extent as compared to pure untreated LCH and simple mixture of oil and surfactant. This piece of research strongly established the need for biorelevant dissolution interphase to differentiate between the formulations.